The Role Of The Sub-District Government in Overcoming Social Order Disturbances in Banyuputih Sub-District, Situbondo Regency - Moh. Ali Imron; Priyanto Priyanto; Dian Ferriswara; Sri Kamariyah (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to describe and analyze: The Role of the District Government in Overcoming Social Order Disturbances, the Obstacles Faced by the District Government in Overcoming Social Order Disturbances and the Solutions Carried Out in Overcoming Obstacles. This research is a qualitative research with a level of descriptive analysis, with data collection techniques using interviews, observations, and documentation. Data analysis techniques Interactive data analysis. The results of the study show that the Village Government Strategy in an Effort to Improve Village Development in Mahakam Regency is carried out with several steps, namely development planning is carried out based on the village development plan musaywarah from the lowest scope, namely RT/RW. The implementation of development is carried out based on the Development Budget Plan, namely what priorities will be implemented, which are locally managed by village self-management, village cooperation with third parties. The process of monitoring and evaluation of development is carried out at the village and sub-district levels assisted by community institutions that check the list of activities listed in the Development Work Plan document stipulated in the Village Budget. The development supervision process is carried out through community institutions and community leaders. The obstacles faced in the development of villages in Mahakam Regency include the lack of achieving the desired development, this is due to the difficulty of obtaining funds. Efforts made include proposing a village Musrenbang next year, making a medium-term long-term development plan for a term of 5 years and including RKA and RKP